The Antibacterial Activity Of Zno Nanoparticles Against Propionibacterium Acnes - M. SHAILAJA RAJ; P.ROSELIN (International Journal of Pharma and Bio Sciences, 2012)
Propionibacterium acnes, a gram positive, non motile, non sporulating and microaerophilic bacillus is normally present on human skin that causes acne. The present treatment for acne though effective, has side effects hence there is a need to find a novel and appropriate method to treat acne. The present study evaluated the antimicrobial activity of ZnO (Zinc Oxide) nanoparticles against Propionibacterium acnes that causes acne. First, P.acnes was isolated from different individuals suffering with acne. It was characterized by using various biochemical characters. The antimicrobial study of ZnO nanoparticles prepared in methanol demonstrated that the ZnO nanoparticles were effective against P.acnes. Then the ZnO nanoparticles were incorporated into cold cream to aid the delivery to P.acnes. It was demonstrated that the antimicrobial activity of the emulsion was very effective and well maintained. Since nanosized ZnO has been used in sunscreens (coatings and paints) because of its transparency to visible light and exhibits strong antibacterial activities on a broad spectrum of bacteria, ZnO nanoparticles have great potential of becoming safe and effective for topical application in treating acne vulgaris and other P.acnes associated diseases.